Aberrant B‐lymphocyte responses in lupus: inherent or induced and potential therapeutic targets. (23rd May 2013) - Taher, Taher E.; Muhammad, Hawzheen A.; Rahim, Asad; Flores‐Borja, Fabian; Renaudineau, Yves; Isenberg, David A.; Mageed, Rizgar A.
Abstract: Background: Lupus is a prototype autoimmune disease of unknown aetiology. The disease is complex; manifest diverse clinical symptoms and disease mechanisms. This complexity has provided many leads to explore: from disease mechanisms to approaches for therapy. B‐lymphocytes play a central role in the pathogenesis of the disease. However, the cause of aberrant B‐lymphocyte responses in patients and, indeed, its causal relationship with the disease remain unclear. Design: This article provides a synopsis of current knowledge of immunological abnormalities in lupus with an emphasis on abnormalities in the B‐lymphocyte compartment. Results: There is evidence for abnormalities in most compartments of the immune system in animal models and patients with lupus including an ever expanding list of abnormalities within the B‐lymphocyte compartment. In addition, recent genome‐wide linkage analyses in large cohorts of patients have identified new sets of genetic association factors some with potential links with defective B‐lymphocyte responses although their full pathophysiological effects remain to be determined. The accumulating knowledge may help in the identification and application of new targeted therapies for treating lupus disease. Conclusions: Cellular, molecular and genetic studies have provided significant insights into potential causes of immunological defects associated with lupus. Most of this insight relate to defects in B‐ and T‐lymphocyte tolerance, signalling and responses. For B‐lymphocytes, there is evidence for altered regulation of inter and intracellular signalling pathways at multiple levels. Some of these abnormalities will be discussed within the context of potential implications for disease pathogenesis and targeted therapies.